ANALISIS INTEGRASI PASAR SPASIAL KOMODITI PANGAN ANTAR PROVINSI DI INDONESIA - Arnanto Arnanto; Sri Hartoyo; Wiwiek Rindayati (IPB University, 2014)
Food prices stabilization through the food production and trade to fulfillment consumption in terms of both availability and accessibility food is government major problem. Government’s ability to determine an appropriate pricing policy depends on market structure, behavior and effectiveness. Trade barriers and market failure reduction, improved access information would make market integration effective and efficient. This study aims to analyze the market integration and the price transmission elasticity that occurs between regions in Indonesia. Using Ravallion integration analysis and a span from 2009 to 2013 on 33 provinces retail prices data in Indonesia to capture level integration and price transmission between regions. The results showed in the rice shows that Jakarta and South Sulawesi region is becoming the leading market and Jakarta for sugar market those integrated with most areas in Indonesia. Sugar and rice have a better degree of integration than soya. Integration analysis with Ravallion models cannot explain two areas integrated or not. It is necessary to study towards further for East Java in terms of either regional autonomy policy or any market failure that occurs in order to find a policy solution to be more integrated. Key words : Food, Market integration, Ravallion model